Crosslinker composition for olefin copolymer, sealant composition for optical device containing same, and sealant film for optical device

By using tetraallyloxysilane and triallyl isocyanurate in olefin-based copolymers, the crosslinking agent composition is optimized, and miscibility deterioration in olefin-based copolymer encapsulation agents and the deterioration of miscibility in olefin-based copolymer encapsulation agents and The problem of low productivity achieves rapid impregnation and high volume resistance optical device encapsulators.

CN119278232APending Publication Date: 2025-01-07LG CHEM LTD

Patent Information

Application Number
CN202380042157.8
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Priority Date
2022-07-11
Filing Date
2023-07-10
Publication Date
2025-01-07

AI Technical Summary

Technical Problem

The existing olefin copolymers have problems of deterioration in miscibility and low productivity in solar cell encapsulators, especially the poor miscibility of ethylene/α-olefin copolymers and polar crosslinking agents, resulting in a long impregnation time, which affects production. efficiency.

Method used

A crosslinking agent composition for olefin copolymers containing tetraallyloxysilane as a promoter is adopted, and combined with a second promoter such as triallyl isocyanurate, by optimizing the assisted crosslinking The ratio and composition of the agent to the crosslinking agent can improve miscibility and crosslinking degree and shorten the impregnation time.

Benefits of technology

It realizes rapid impregnation in olefin copolymers, improves the volume resistance and light transmittance of the encapsulator composition for optical devices, and improves production efficiency and product performance.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure BDA0005147353090000031
    Figure BDA0005147353090000031
  • Figure BDA0005147353090000041
    Figure BDA0005147353090000041
  • Figure BDA0005147353090000051
    Figure BDA0005147353090000051
Patent Text Reader

Abstract

The present invention relates to a cross-linking agent composition for an olefin copolymer, a sealing agent composition for an optical device, a sealing agent film for an optical device, and an optoelectronic device, in which a compound of formula 1 is applied as an assistant cross-linking agent to a cross-linking agent composition for an olefin copolymer containing an olefin copolymer or to a sealing agent composition for an optical device, thus, an encapsulant composition for optical devices and an encapsulant film for optical devices are formed, which exhibit excellent productivity, high volume resistance and high light transmittance.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] This application claims the benefit of Korean Patent Application No. 10-2022-0085135 filed on July 11, 2022, in the Korean Intellectual Property Office, the contents of which are incorporated herein by reference.

[0002] The present invention relates to a crosslinking agent composition for an olefin copolymer, an encapsulant composition for an optical device and an encapsulant film for an optical device containing the crosslinking agent composition for an olefin copolymer, and further relates to a crosslinking agent composition for an olefin copolymer used in an encapsulant composition for an optical device containing an olefin copolymer, an encapsulant composition for an optical device containing a crosslinking agent, an optical device module manufactured using the crosslinking agent, and an optical device module containing an encapsulant film for an optical device. Background Art

[0003] As global environmental problems and energy problems become increasingly severe, solar cells have attracted attention as a way to produce clean energy without worrying about exhaustion. If solar cells are used outdoors (such as on the roof of a building), module types are generally used. When manufacturing solar cell modules, in order to obtain crystalline solar cell modules, the protective sheet for solar cell modules (transparent protective component on the surface side) / solar cell encapsulant / crystalline solar cell device / solar cell encapsulant / protective sheet for solar cell modules (transparent protective component on the back side) are stacked in this order. At the same time, in order to manufacture thin-film solar cell modules, thin-film solar cell devices / solar cell encapsulants / protective sheets for solar cell modules are stacked in this order.

[0004] As a solar cell encapsulant, ethylene / vinyl acetate copolymer or ethylene / α-olefin copolymer is generally used. In addition, in the solar cell encapsulant, considering the need for long-term weather resistance, a light stabilizer is generally included as an additive. In addition, considering the adhesion of a transparent surface side protective member or a back side protective member represented by glass, a silane coupling agent is generally added to the solar cell encapsulant.

[0005] In particular, ethylene / vinyl acetate copolymer (EVA) has been widely used due to its excellent transparency, flexibility and adhesion. Ethylene / vinyl acetate copolymer (EVA) has been widely used due to its excellent transparency, flexibility and adhesion. However, if the EVA composition is used as a constituent material of a solar cell encapsulant, it has been recognized that components such as acetic acid gas produced by the decomposition of EVA may affect the solar cell device.

[0006] Ethylene / α-olefin copolymers do not have problems related to resin hydrolysis and can solve problems of life or reliability degradation. However, since ethylene / α-olefin copolymers do not contain polar groups in the resin, miscibility with polar cross-linking aids contained as a constituent material of a conventional solar cell encapsulant deteriorates, so the time required for impregnation is long and there is a problem of productivity.

[0007] As described above, there is still a need to develop a co-crosslinking agent capable of improving the productivity of a solar cell encapsulant comprising an ethylene / α-olefin copolymer that can be effectively used as a material having excellent volume resistivity and desired high insulation properties, such as a solar cell encapsulant.

[0008] [Prior art literature]

[0009] [Patent Document]

[0010] (Patent Document 1) Korean Patent Publication No. 2018-0063669 Summary of the invention

[0011] Technical issues

[0012] The task to be solved by the present invention is to provide a crosslinking agent composition for an olefin copolymer, which is used for crosslinking an olefin copolymer and contains an auxiliary crosslinking agent having excellent miscibility with the olefin copolymer.

[0013] Another task to be solved by the present invention is to provide an encapsulant composition for an optical device, which contains a co-crosslinking agent having excellent miscibility with an olefin-based copolymer and exhibits high volume resistance and thus excellent insulation properties.

[0014] Another task to be solved by the present invention is to provide an encapsulant film for an optical device produced by using the encapsulant composition for an optical device.

[0015] Another object to be solved by the present invention is to provide an optoelectronic device comprising the encapsulant film for an optical device.

[0016] Technical Solution

[0017] In order to achieve the above-mentioned objectives, the present invention provides a crosslinking agent composition for an olefin copolymer, an encapsulant composition for an optical device, an encapsulant film for an optical device, and an optoelectronic device.

[0018] [1] The present invention provides a crosslinking agent composition for an olefin copolymer, which comprises a compound of Formula 1.

[0019] [Formula 1]

[0020]

[0021] In Formula 1, R1 to R4 are each independently an alkyl group of 1 to 20 carbon atoms or an alkenyl group of 2 to 20 carbon atoms, wherein two or more R1 to R4 are each independently an alkenyl group of 2 to 20 carbon atoms.

[0022] [2] The present invention provides the crosslinking agent composition for an olefin copolymer according to [1], wherein R1 to R4 are independently alkenyl groups having 2 to 20 carbon atoms.

[0023] [3] The present invention provides the crosslinking agent composition for an olefin copolymer according to [1] or [2], wherein R1 to R4 are each independently an alkenyl group having 2 to 8 carbon atoms and having a double bond at the terminal.

[0024] [4] The present invention provides a crosslinking agent composition for an olefin copolymer as described in any one of [1] to [3], wherein the auxiliary crosslinking compound of Formula 1 is tetraallyloxysilane.

[0025] [5] The present invention provides the crosslinking agent composition for an olefin copolymer of [4], further comprising a second crosslinking aid compound in addition to the crosslinking aid compound of formula 1.

[0026] [6] The present invention provides a crosslinking agent composition for a polyolefin copolymer according to [5], wherein the weight ratio of the auxiliary crosslinking compound of formula 1 to the second auxiliary crosslinking compound is 1:0.2 to 1:9.0.

[0027] [7] The present invention provides a crosslinking agent composition for a polyolefin copolymer according to [5] or [6], wherein the second auxiliary crosslinking compound comprises one or more selected from the group consisting of triallyl isocyanurate, triallyl cyanurate, diallyl phthalate, diallyl fumarate, diallyl maleate, ethylene glycol diacrylate, ethylene glycol dimethacrylate and trimethylolpropane trimethacrylate.

[0028] [8] The present invention provides a crosslinking agent composition for a polyolefin copolymer according to any one of [1] to [7], wherein the crosslinking agent is one or more selected from the group consisting of organic peroxides, hydroperoxides and azo compounds.

[0029] [9] The present invention provides a crosslinking agent composition for a polyolefin copolymer according to any one of [1] to [8], wherein the crosslinking agent is selected from the group consisting of tert-butyl isopropyl peroxide, di-tert-butyl peroxide, diisopropyl peroxide, 2,5-dimethyl-2,5-di(tert-butylperoxy)hexane, 2,5-dimethyl-2,5-di(tert-butylperoxy)-3-hexyne, isopropyl hydroperoxide, diisopropyl hydroperoxide, 2,5-dimethyl-2,5-di(hydroperoxy)hexane, tert-butyl hydroperoxide, bis(3,5,5-trimethylhexanoyl)peroxide, octanoyl peroxide, benzoyl peroxide, o-methylbenzoyl peroxide, One or more selected from the group consisting of 2,4-dichlorobenzoyl oxide, tert-butyl peroxide isobutyrate, tert-butyl peroxide acetate, tert-butyl peroxycarbonate 2-ethylhexyl tert-butyl ester (TBEC), tert-butyl peroxide 2-ethylhexanoate, tert-butyl peroxide pivalate, tert-butyl peroxide octanoate, tert-butyl peroxycarbonate isopropyl tert-butyl peroxide, tert-butyl peroxide benzoate, tert-butyl peroxide phthalate, 2,5-dimethyl-2,5-di(benzoylperoxy)hexane, 2,5-dimethyl-2,5-di(benzoylperoxy)-3-hexyne, methyl ethyl ketone peroxide, cyclohexanone peroxide, azobisisobutyronitrile and azobis(2,4-dimethylvaleronitrile).

[0030]

[10] The present invention provides a crosslinking agent composition for a polyolefin copolymer according to any one of [1] to [9], wherein the silane coupling agent is one or more selected from the group consisting of N-(β-aminoethyl)-γ-aminopropyltrimethoxysilane, N-(β-aminoethyl)-γ-aminopropylmethyldimethoxysilane, γ-aminopropyltriethoxysilane, γ-glycidoxypropyltrimethoxysilane, γ-methacryloxypropyltrimethoxysilane, vinyltrimethoxysilane, vinyltriethoxysilane, 3-methacryloxypropylmethyldimethoxysilane, 3-methacryloxypropylmethyldimethoxysilane, 3-methacryloxypropyltriethoxysilane and p-phenylvinyltrimethoxysilane.

[0031]

[11] In addition, the present invention also provides an encapsulant composition for an optical device, comprising an olefin-based polymer; and the crosslinking agent composition for an olefin-based copolymer according to any one of [1] to

[10] .

[0032]

[12] The present invention provides the encapsulant composition for an optical device according to

[11] , wherein the olefin copolymer is an ethylene / α-olefin copolymer.

[0033]

[13] In addition, the present invention provides an encapsulant film for an optical device, which contains a structure derived from an olefin-based copolymer and a compound of Formula 1.

[0034] [Formula 1]

[0035]

[0036] In Formula 1, R1 to R4 are each independently an alkyl group of 1 to 20 carbon atoms or an alkenyl group of 2 to 20 carbon atoms, wherein two or more R1 to R4 are each independently an alkenyl group of 2 to 20 carbon atoms.

[0037]

[14] Furthermore, the present invention provides an optoelectronic device comprising an optical device and the encapsulant film for an optical device of

[13] .

[0038] Beneficial Effects

[0039] The crosslinking agent composition for olefin copolymers of the present invention contains a compound having excellent miscibility with the olefin copolymer as a co-crosslinking agent and has the characteristic of rapid penetration into the olefin copolymer. The encapsulant composition for optical devices obtained using the composition has excellent volume resistivity and light transmittance and can be widely used for various purposes in the electrical and electronic industries. DETAILED DESCRIPTION

[0040] Hereinafter, the present invention will be described in more detail to help understanding of the present invention.

[0041] It should be understood that the words or terms used in the present invention and claims should not be interpreted as the meanings defined in commonly used dictionaries. It should also be understood that based on the principle that the inventor can appropriately define the meanings of words or terms to best explain the invention, the words or terms should be interpreted as having the meanings consistent with them in the relevant technical background and the technical concept of the present invention.

[0042] Each substituent defined in the present invention will be explained in detail below.

[0043] The term "alkyl" used in the present invention refers to a straight-chain or branched hydrocarbon residue, unless otherwise specified.

[0044] The term "alkenyl" used in the present invention refers to a straight chain or branched chain alkenyl group unless otherwise specified.

[0045] The branched chain may be an alkyl group of 1 to 20 carbon atoms or an alkenyl group of 2 to 20 carbon atoms.

[0046] Crosslinking agent composition for olefin copolymer

[0047] The cross-linking agent composition for an olefin copolymer comprises: a cross-linking agent; a silane coupling agent; and a cross-linking auxiliary compound represented by Formula 1.

[0048] [Formula 1]

[0049]

[0050] In Formula 1, R1 to R4 are each independently an alkyl group of 1 to 20 carbon atoms or an alkenyl group of 2 to 20 carbon atoms, wherein two or more R1 to R4 are each independently an alkenyl group of 2 to 20 carbon atoms.

[0051] In addition, in Formula 1, R1 to R4 may each independently be an alkenyl group having 2 to 20 carbon atoms.

[0052] In addition, in Formula 1, R1 to R4 may each independently be an alkenyl group of 2 to 8 carbon atoms having a double bond at its terminal.

[0053] In addition, the cross-linking agent composition for an olefin-based copolymer according to one embodiment of the present invention may particularly include tetraallyloxysilane represented by the following Formula 2 as the compound of Formula 1.

[0054] [Formula 2]

[0055]

[0056] The compound of formula 1 contained in the crosslinking agent composition for olefin copolymers of the present invention can be included in the crosslinking agent composition for olefin copolymers as a co-crosslinking agent, and the compound of formula 1 can show excellent miscibility with the olefin copolymers, and can also show excellent impregnation rate. Thus, the absorption rate of the co-crosslinking agent with the slowest absorption rate in the olefin copolymer among the crosslinking agent, silane coupling agent and co-crosslinking agent contained in the conventional crosslinking agent composition for olefin copolymers can be improved, the impregnation time of the crosslinking agent composition can be shortened, a shorter immersion time can be achieved, and the olefin copolymer can show excellent crosslinking characteristics.

[0057] If the crosslinking agent composition for an olefin-based copolymer of the present invention containing the compound of Formula 1 is used as a crosslinking agent in an optical device encapsulant composition containing an olefin-based copolymer, the optical device encapsulant composition can exhibit a high degree of crosslinking, high volume resistance, and high light transmittance.

[0058] In addition, the cross-linking agent composition for an olefin-based copolymer may further include a second cross-linking aid compound in addition to the cross-linking aid compound of Formula 1 as a cross-linking aid.

[0059] As the second auxiliary cross-linking agent, various auxiliary cross-linking agents known in the art may be used, and a compound containing at least one or more unsaturated groups such as an allyl group or a (meth)acryloyloxy group may be used.

[0060] The second auxiliary cross-linking agent can be an auxiliary cross-linking agent containing at least one or more unsaturated groups, and can be, for example, a polyallyl compound, such as triallyl isocyanurate (TAIC), triallyl cyanurate, diallyl phthalate, diallyl fumarate and diallyl maleate, and the compound containing (meth)acryloyloxy group can include, for example, a poly(meth)acryloyloxy compound, such as ethylene glycol diacrylate, ethylene glycol dimethacrylate and trimethylolpropane trimethacrylate, without specific limitation.

[0061] If the crosslinking agent composition for olefin-based copolymers according to one embodiment of the present invention further includes a second auxiliary crosslinking compound in addition to the compound of Formula 1, the weight ratio of the compound of Formula 1 to the second auxiliary crosslinking compound may be 1:0.20 to 9.0, specifically, 1:0.20 to 6.0, 1:0.20 to 5.0, 1:0.20 to 4.0, 1:0.20 to 3.7, 1:0.25 to 5.0, 1:0.25 to 4.0, 1:0.25 to 3.7, 1:0.25 to 3.5, 1:0.25 to 3.2, 1:0.25 to 3.0, 1:0.3 to 3.7, 1:0.3 to 3.5, 1:0.3 to 3.2, 1:0.3 to 3.0, or 1:0.33 to 3.0.

[0062] If the cross-linking agent composition for olefin copolymers according to one embodiment of the present invention contains both the compound of Formula 1 and the second auxiliary cross-linking compound, a higher degree of cross-linking can be achieved compared with the case where only the same amount of the compound of Formula 1 is included. If applied to an encapsulant composition for optical devices, the encapsulant composition for optical devices can exhibit high volume resistance and can satisfy excellent light transmittance and adhesive strength.

[0063] If the compound of formula 1 and the second co-crosslinking agent are contained at the same time, and if the ratio of the second co-crosslinking agent to the compound of formula 1 is increased to a certain extent or more, the degree of crosslinking can be increased and the vulcanization characteristics can be improved. If the ratio of the second co-crosslinking agent to the compound of formula 1 is reduced, the impregnation rate can be reduced. Therefore, the appropriate ratio can be determined within a certain range according to the physical properties required to be exhibited. If the ratio of the second co-crosslinking agent is too large, it may be difficult to reflect the effect of improving the impregnation rate by using the compound of formula 1. If the ratio of the second co-crosslinking agent is too small, it may be difficult to reflect the additional effect that can be achieved by mixing the second co-crosslinking agent.

[0064] In the crosslinking agent composition for olefin copolymers of one embodiment of the present invention, in order to reduce the impregnation time of the crosslinking agent and have excellent vulcanization performance, crosslinking degree, light transmittance and bonding strength, the compound of formula 1 and the second auxiliary crosslinking compound can be simultaneously included, and the weight ratio of the compound of formula 1 and the second auxiliary crosslinking compound is 1:0.20 to 3.7, especially, 1:0.25 to 3.7, 1:0.25 to 3.5, 1:0.25 to 3.2, 1:0.25 to 3.0, 1:0.3 to 3.7, 1:0.3 to 3.5, 1:0.3 to 3.2, 1:0.3 to 3.0, or 1:0.33 to 3.0. The crosslinking agent can use various crosslinking agents known in the art, as long as they are crosslinkable compounds that can initiate free radical polymerization or form crosslinked bonds, and can use one or more selected from the group consisting of organic peroxides, hydroperoxides and azo compounds.

[0065] Furthermore, in one embodiment of the present invention, the crosslinking agent may be, in particular, an organic peroxide.

[0066] The organic peroxide may be an organic peroxide having a one-hour half-life temperature of 120° C. to 135° C., for example, 120° C. to 130° C., 120° C. to 125° C., and particularly 121° C. “One-hour half-life temperature” refers to a temperature at which the half-life of the crosslinking agent is one hour. The temperature at which the free radical initiation reaction is effectively carried out may become different depending on the one-hour half-life temperature. Therefore, in the case of using an organic peroxide having a one-hour half-life temperature in the above range, the free radical initiation reaction, that is, the crosslinking reaction, can be effectively carried out at the lamination process temperature for manufacturing an optoelectronic device.

[0067] The crosslinking agent may include one or more selected from the group consisting of: dialkyl peroxides, such as tert-butyl isopropyl peroxide, di-tert-butyl peroxide, di-isopropyl peroxide, 2,5-dimethyl-2,5-di(tert-butylperoxy)hexane and 2,5-dimethyl-2,5-di(tert-butylperoxy)-3-hexyne; hydroperoxides, such as isopropyl hydroperoxide, diisopropyl hydroperoxide, 2,5-dimethyl-2,5-di(hydroperoxy)hexane, tert-butyl hydroperoxide, etc.; diacyl peroxides, such as di-3,5,5-trimethylhexanoyl peroxide, octanoyl peroxide, benzoyl peroxide, o-methylbenzoyl peroxide, 2,4-dichlorobenzoyl peroxide ; peroxyesters such as tert-butyl peroxyisobutyrate, tert-butyl peracetate, tert-butyl peroxycarbonate 2-ethylhexyl ester (TBEC), tert-butyl peroxy 2-ethylhexanoate, tert-butyl peroxypivalate, tert-butyl peroxyoctanoate, tert-butyl peroxyisopropyl carbonate, tert-butyl peroxybenzoate, di-tert-butyl peroxyphthalate, 2,5-dimethyl-2,5-di(benzoylperoxy)hexane and 2,5-dimethyl-2,5-di(benzoylperoxy)-3-hexyne, etc.; ketone peroxides such as methyl ethyl ketone peroxide, cyclohexanone peroxide, etc.; lauroyl peroxide; and azo compounds such as azobisisobutyronitrile, azobis(2,4-dimethylvaleronitrile), and are not limited thereto.

[0068] The silane coupling agent that can be used is, for example, one or more selected from the group consisting of N-(β-aminoethyl)-γ-aminopropyltrimethoxysilane, N-(β-aminoethyl)-γ-aminopropylmethyldimethoxysilane, γ-aminopropyltriethoxysilane, γ-glycidoxypropyltrimethoxysilane, γ-methacryloxypropyltrimethoxysilane (MEMO), vinyltrimethoxysilane, vinyltriethoxysilane, 3-methacryloxypropylmethyldimethoxysilane, 3-methacryloxypropylmethyldimethoxysilane, 3-methacryloxypropyltriethoxysilane and p-phenylvinyltrimethoxysilane.

[0069] The crosslinking agent composition for olefin copolymers may contain 20 to 80 parts by weight of a crosslinking agent, 5 to 30 parts by weight of a silane coupling agent, and 10 to 60 parts by weight of an auxiliary crosslinking agent containing the auxiliary crosslinking agent of Formula 1. The amount of each component may refer to the relative proportion of the weight of the component contained in the crosslinking agent composition for olefin copolymers.

[0070] In the crosslinking agent composition for olefin copolymers, the content of the crosslinking agent may be 20 parts by weight to 80 parts by weight, in particular, more than 20 parts by weight, more than 25 parts by weight, more than 30 parts by weight, more than 35 parts by weight, more than 40 parts by weight, and less than 80 parts by weight, less than 75 parts by weight, or less than 70 parts by weight. If the content of the crosslinking agent is too low, it is difficult to carry out a crosslinking reaction when using a polyolefin copolymer; if the content of the crosslinking agent is too high, the volume resistance of the encapsulant composition for optical devices manufactured using the polyolefin copolymer may be reduced. Therefore, if the content of the crosslinking agent contained in the crosslinking agent composition for olefin copolymers is within the above range, the encapsulant composition for optical devices using the composition can undergo an appropriate crosslinking reaction to form an encapsulant for optical devices, and the encapsulant for optical devices manufactured thereby can exhibit a higher volume resistance.

[0071] The content of the silane coupling agent in the crosslinking agent composition for olefin copolymers may be 5 to 30 parts by weight, in particular, more than 5 parts by weight, more than 6 parts by weight, more than 7 parts by weight, more than 8 parts by weight, and less than 20 parts by weight, less than 19 parts by weight, or less than 18 parts by weight. If the content of the silane coupling agent is too little, and if a polyolefin copolymer is used, the adhesion of the encapsulant composition for optical devices to the substrate (for example, the adhesion of the encapsulant composition for optical devices to the glass substrate) is low, and it is difficult to show the appropriate performance as an encapsulant for optical devices. If the content of the silane coupling agent is too large, the volume resistance of the encapsulant for optical devices may not be properly reduced. If the content of the silane coupling agent in the crosslinking agent composition for olefin copolymers is within the above range, the encapsulant composition for optical devices using the composition can show excellent adhesion to the optical device substrate or the glass substrate where the optical device is located, can effectively prevent moisture penetration, the optical device can maintain excellent performance for a long time, and the encapsulant for optical devices can show a higher volume resistance.

[0072] The total amount of the auxiliary cross-linking agent including the auxiliary cross-linking compound of formula 1, that is, the total amount of the auxiliary cross-linking compound of formula 1 as the auxiliary cross-linking agent contained in the cross-linking agent composition for polyolefin copolymers, or the total amount of the auxiliary cross-linking compound of formula 1 and the second auxiliary cross-linking compound can be 10 parts by weight to 60 parts by weight, especially more than 11 parts by weight, more than 12 parts by weight, more than 13 parts by weight and less than 60 parts by weight, less than 55 parts by weight, or less than 50 parts by weight.

[0073] For example, the olefin copolymer to which the cross-linking agent composition for an olefin copolymer can be applied may satisfy, for example, a) a density of 0.85 g / cc to 0.90 g / cc, and (b) a melt index of 0.1 g / 10 min to 100 g / 10 min.

[0074] The density (a) of the olefin copolymer may be particularly 0.850 g / cc or more, 0.855 g / cc or more, 0.860 g / cc or more, 0.865 g / cc or more, or 0.870 g / cc or more, and 0.900 g / cc or less, 0.895 g / cc or less, 0.890 g / cc or less, 0.885 g / cc or less, or 0.880 g / cc or less. If the density of the olefin copolymer is too high, the optical device encapsulant composition using the same and the optical device encapsulant manufactured by using the same may be reduced due to the crystalline phase contained in the olefin copolymer, but if the olefin copolymer satisfies the above density range, high light transmittance can be exhibited.

[0075] The (b) melt index of the olefin copolymer may be 0.1 g / 10 min or more, 0.5 g / 10 min or more, 1.0 g / 10 min or more, 1.5 g / 10 min or more, 2.0 g / 10 min or more, 2.5 g / 10 min or more, 5.0 g / 10 min or more, or 10.0 g / 10 min or more, and 100 g / 10 min or less, 95 g / 10 min or less, 90 g / 10 min or less, 85 g / 10 min or less, 80 g / 10 min or less, 75 g / 10 min or less, 70 g / 10 min or less, 60 g / 10 min or less, or 50 g / 10 min or less. If the melt index of the olefin copolymer deviates from the above range and is too low or too high, there may be a problem that the moldability of the encapsulant composition for optical devices may be deteriorated and stable extrusion may be difficult. However, if the olefin-based copolymer satisfies the above melt index range, the optical device encapsulant composition may have excellent moldability, and an optical device encapsulant and an optical device encapsulant sheet can be stably extruded.

[0076] The olefin copolymer used in the cross-linking agent composition for an olefin copolymer according to one embodiment of the present invention may be, in particular, an ethylene / α-olefin copolymer.

[0077] Generally, the density of ethylene / α-olefin copolymers can be affected by the type and content of the monomers used in the polymerization process, the degree of polymerization, etc., and in the case of copolymers, the content of comonomers has a greater impact. As the content of comonomers increases, low-density ethylene / α-olefin copolymers can be prepared, and the content of comonomers that can be introduced into the copolymer can depend on the inherent copolymerization properties of the catalyst.

[0078] The ethylene / α-olefin copolymer to which the cross-linking agent composition for an olefin copolymer of the present invention is applied can show low density and excellent processability as described above.

[0079] The ethylene / α-olefin copolymer is prepared by copolymerizing ethylene and an α-olefin-based monomer, and in this case, the α-olefin representing the part derived from the α-olefin-based monomer in the copolymer may be an α-olefin of 3 to 20 carbon atoms, particularly propylene, 1-butene, 1-pentene, 4-methyl-1-pentene, 1-hexene, 1-heptene, 1-octene, 1-decene, 1-undecene, 1-dodecene, 1-tetradecene, 1-hexadecene, 1-eicosene, etc., and any one thereof or a mixture of two or more thereof may be used. Among them, the α-olefin may be 1-butene, 1-hexene or 1-octene, particularly 1-butene, 1-hexene or a combination thereof.

[0080] In addition, in the ethylene / α-olefin copolymer, the α-olefin content may be appropriately selected within the range satisfying physical conditions without limitation, and is particularly greater than 0 mol% to 99 mol%, or 10 mol% to 50 mol%.

[0081] In addition, the olefin copolymer may have a volume resistivity of 1.0×10 15 Ω·cm or more ethylene / α-olefin copolymers, particularly 3.0×10 15 Ω·cm or more, 5.0×10 15 Ω cm, or 7.0 × 10 15 Ω·cm or more. If the volume resistivity of the olefin copolymer is too low, the volume resistivity of the encapsulant composition for optical devices may not reach a suitable level after crosslinking, but if the volume resistivity of the olefin copolymer satisfies the above value, the encapsulant composition for optical devices may exhibit excellent volume resistivity after crosslinking. There is no specific upper limit on the volume resistivity of the olefin copolymer, but considering the volume resistivity generally exhibited by the olefin copolymer and the difficulty in preparing an olefin copolymer with high volume resistivity, it may be 9.9×10 17 Ω·cm or less, 9.0×10 17 Ω·cm or less, 7.0×10 17 Ω·cm or less.

[0082] Encapsulant composition for optical device

[0083] The crosslinking agent composition for olefin copolymers of the present invention can be used together with olefin copolymers to form an encapsulant composition for optical devices. The present invention provides an encapsulant composition for optical devices, which comprises an olefin-based polymer and a crosslinking agent composition for olefin copolymers.

[0084] The explanations about the olefin copolymer and the encapsulant composition for an optical device are the same as those described above.

[0085] Based on 100 parts by weight of the encapsulant composition for optical devices, the content of the olefin copolymer may be 80 parts by weight to 99.5 parts by weight, particularly 80 parts by weight or more, 82 parts by weight or more, 85 parts by weight or more, 86 parts by weight or more, 87 parts by weight or more, or 88 parts by weight or more, and 99.5 parts by weight or less, 99 parts by weight or less, or 98.5 parts by weight or less. If the amount of the olefin copolymer contained in the encapsulant composition for optical devices is too low, it may be difficult to exhibit suitable mechanical properties of the encapsulant for optical devices, such as tear resistance and tear strength. If the content of the olefin copolymer in the encapsulant composition for optical devices is within the above range, it can exhibit suitable mechanical properties as an encapsulant for optical devices.

[0086] Based on 100 parts by weight of the olefin copolymer, the amount of the crosslinking agent composition for the olefin copolymer of one embodiment of the present invention may be 0.5 parts by weight to 20 parts by weight. Based on 100 parts by weight of the olefin copolymer, the amount of the crosslinking agent composition for the olefin copolymer may be particularly 0.5 parts by weight or more, 0.7 parts by weight or more, 0.8 parts by weight or more, 1 part by weight or more, 1.1 parts by weight or more, 1.2 parts by weight or more, 1.3 parts by weight or more, 1.4 parts by weight or more, or 1.5 parts by weight or more, and 20 parts by weight or less, 18 parts by weight or less, 15 parts by weight or less, 10 parts by weight or less, 8 parts by weight or less, 6 parts by weight or less, 5 parts by weight or less, or 3 parts by weight or less. If the amount of the crosslinking agent composition is too small relative to the olefin copolymer, it is difficult to cause a crosslinking reaction; if the amount of the crosslinking agent composition is too large, the volume resistance of the encapsulant for optical devices may be reduced. If the ratio of the crosslinking agent composition to the olefin copolymer is as described above, the optical device encapsulant composition using the crosslinking agent composition can undergo an appropriate crosslinking reaction to form an optical device encapsulant, and the optical device encapsulant thus produced can exhibit a high volume resistivity.

[0087] In the encapsulant composition for optical devices of one embodiment of the present invention, the content of the auxiliary cross-linking compound of Formula 1 may be 0.1 to 9 parts by weight based on 100 parts by weight of the olefin copolymer. Based on 100 parts by weight of the polyolefin copolymer, the content of the auxiliary cross-linking compound of Formula 1 may be specifically 0.1 parts by weight or more, 0.2 parts by weight or more, 0.3 parts by weight or more, or 0.4 parts by weight or more, and 9 parts by weight or less, 8 parts by weight or less, 7 parts by weight or less, 6 parts by weight or less, 5 parts by weight or less, 4 parts by weight or less, 3 parts by weight or less, or 2 parts by weight or less. If the auxiliary cross-linking compound of Formula 1 and the second auxiliary cross-linking compound are used together as auxiliary cross-linking agents, the total amount may meet the above range. If the amount of the auxiliary cross-linking agent relative to the olefin copolymer is too small, it is difficult to induce a cross-linking reaction; if the amount of the auxiliary cross-linking agent is too large, the volume resistance of the encapsulant for optical devices may be reduced. If the auxiliary cross-linking agent is contained in the polyolefin-based copolymer at the above ratio, the optical device encapsulant composition can induce an appropriate cross-linking reaction to form an optical device encapsulant, and the thus formed optical device encapsulant can exhibit a high volume resistance.

[0088] Furthermore, the encapsulant composition for an optical device may appropriately contain various additives known in the art in addition to the above-mentioned components.

[0089] As the additive, one or more additives selected from the group consisting of a light stabilizer, an ultraviolet absorber, and a heat stabilizer may be used.

[0090] Depending on the purpose of the applied composition, the light stabilizer can capture active substances initiated by photothermal reaction of the resin to prevent photooxidation. The type of light stabilizer used is not particularly limited, and for example, known compounds such as hindered amine compounds and hindered piperidine compounds can be used.

[0091] The ultraviolet absorber can absorb ultraviolet rays from sunlight or the like and convert them into harmless heat energy within the molecule, depending on the purpose, and plays a role in preventing the photothermally induced active substances in the resin composition from being excited. The specific type of the ultraviolet absorber used is not particularly limited, and for example, one or a mixture of two or more of inorganic ultraviolet absorbers such as benzophenone, benzotriazole, acrylonitrile, metal complex, hindered amine, ultrafine particulate titanium oxide or ultrafine particulate zinc oxide can be used.

[0092] In addition, the thermal stabilizer may include phosphorus-based thermal stabilizers such as tris(2,4-di-tert-butylphenyl)phosphite, bis[2,4-bis(1,1-dimethylethyl)-6-methylphenyl]ethyl phosphite, tetrakis(2,4-di-tert-butylphenyl)[1,1-biphenyl]-4,4'-diylbisphosphonate and bis(2,4-di-tert-butylphenyl)pentaerythritol diphosphite; and lactone-based thermal stabilizers such as the reaction product of 8-hydroxy-5,7-di-tert-butylfuran-2-one and o-xylene, and one or more thereof may be used.

[0093] The content of the light stabilizer, ultraviolet absorber and / or heat stabilizer is not specifically limited. That is, the content of the additive can be appropriately selected in consideration of the use of the resin composition, the shape or density of the additive, etc. Generally, the content of the additive can be appropriately controlled within the range of 0.01 to 5 parts by weight based on 100 parts by weight of the total solid content of the encapsulant composition for optical devices.

[0094] In addition, the encapsulant composition for optical devices can be used in the form of various molded products by molding by injection molding, extrusion, etc. In particular, the composition can be used in various optoelectronic devices, for example, as a sealant for sealing devices in solar cells, and can be used as an industrial material applied to a temperature-increasing lamination process, etc., without limitation.

[0095] Furthermore, the present invention provides an encapsulant film for an optical device produced using the encapsulant composition for an optical device.

[0096] The encapsulant film for an optical device according to one embodiment of the present invention may include a structure derived from an olefin-based copolymer and the auxiliary cross-linking compound of Formula 1.

[0097] [Formula 1]

[0098]

[0099] In Formula 1, R1 to R4 are each independently an alkyl group of 1 to 20 carbon atoms or an alkenyl group of 2 to 20 carbon atoms, wherein two or more R1 to R4 are each independently an alkenyl group of 2 to 20 carbon atoms.

[0100] The descriptions of the olefin copolymer and the auxiliary cross-linking compound of formula 1 are the same as described above.

[0101] In addition, the encapsulant film for an optical device according to another embodiment of the present invention may include a structure derived from the auxiliary cross-linking compound of Formula 1 and a second auxiliary cross-linking compound.

[0102] The description about the second auxiliary cross-linking compound and the description about the case where the auxiliary cross-linking compound of Formula 1 and the second auxiliary cross-linking agent compound are used together as an auxiliary cross-linking agent are the same as described above.

[0103] Furthermore, the present invention provides an optoelectronic device comprising the encapsulant film for an optical device.

[0104] Example

[0105] Hereinafter, the present invention will be explained in more detail with reference to embodiments. However, the embodiments are provided for illustrative purposes only, and the scope of the present invention is not limited thereto.

[0106] Example 1

[0107] Tetraallyloxysilane (TAOS, a product of Gelest) and triallyl isocyanurate (TAIC, a product of Sigma-Aldrich) were mixed in an amount of 25 parts by weight and 75 parts by weight, respectively, to prepare a co-crosslinking agent.

[0108] 500g of LG Chem's LUCENE TM LF675 (ethylene / 1-butene copolymer) was dried in a conventional oven at 40°C overnight. LUCENE measured based on ASTM D1505 TM The density of LF675 is 0.877g / cm 2 , the melt index (190°C, 2.16kg) measured based on ASTM D1238 is 14.0g / 10min. The bowl temperature of the viscometer (Haake Modular TorqueViscometer, product of Thermo Electron (Karsruhe) company) is set to 40°C. The ethylene / α-olefin copolymer is injected into the bowl, and the crosslinker composition [1.00 parts per hundred parts of rubber (phr) of tert-butyl 1-(2-ethylhexyl) monoperoxycarbonate (TBEC, product of Sigma Aldrich Company) as a crosslinker, 0.50phr of a mixture of TAOS and TAIC prepared as a co-crosslinker (weight ratio 25:75), and 0.20phr of methacryloxypropyl trimethoxysilane (MEMO, product of Shinetsu Company) as a silane coupling agent] is injected using an electronic pipette. While stirring at 40° C. and 40 rpm, the change in torque value over time was observed, and when the torque value increased rapidly, the impregnation was terminated and the impregnation completion time of the crosslinking agent composition was measured.

[0109] Thereafter, the impregnated sample was extruded into an average thickness of 0.5 mm using a micro extruder at a low temperature (under an extruder barrel temperature of 90 to 100° C.) at which high-temperature crosslinking could not be achieved to form a sheet-like encapsulant film.

[0110] Example 2

[0111] A co-crosslinking agent was prepared in the same manner as in Example 1 except that tetraallyloxysilane (TAOS) and triallyl isocyanurate (TAIC) were mixed in a mixing ratio of 50 parts by weight to 50 parts by weight, respectively, and then an encapsulant film was manufactured.

[0112] Example 3

[0113] A co-crosslinking agent was prepared in the same manner as in Example 1 except that tetraallyloxysilane (TAOS) and triallyl isocyanurate (TAIC) were mixed in a mixing ratio of 75 parts by weight to 25 parts by weight, respectively, and then an encapsulant film was manufactured.

[0114] Example 4

[0115] An auxiliary cross-linking agent was prepared in the same manner as in Example 1, except that only tetraallyloxysilane (TAOS) was used as the auxiliary cross-linking agent and the injection amount was changed from 0.50 phr to 0.25 phr, and then an encapsulant film was manufactured.

[0116] Example 5

[0117] A co-crosslinking agent was prepared in the same manner as in Example 1, except that only tetraallyloxysilane (TAOS) was used as the co-crosslinking agent, and then an encapsulant film was manufactured.

[0118] Example 6

[0119] An auxiliary cross-linking agent was prepared in the same manner as in Example 1, except that only tetraallyloxysilane (TAOS) was used as the auxiliary cross-linking agent and the injection amount was changed from 0.50 phr to 1.00 phr, and then an encapsulant film was manufactured.

[0120] Example 7

[0121] A co-crosslinking agent was prepared in the same manner as in Example 1 except that tetraallyloxysilane (TAOS) and triallyl isocyanurate (TAIC) were mixed in a mixing ratio of 10 parts by weight to 90 parts by weight, respectively, and then an encapsulant film was manufactured.

[0122] Example 8

[0123] A co-crosslinking agent was prepared in the same manner as in Example 1 except that tetraallyloxysilane (TAOS) and triallyl isocyanurate (TAIC) were mixed in a mixing ratio of 20 parts by weight to 80 parts by weight, respectively, and then an encapsulant film was manufactured.

[0124] Comparative Example 1

[0125] A co-crosslinking agent was prepared in the same manner as in Example 1, except that only triallyl isocyanurate (TAIC) was used as the co-crosslinking agent, and then an encapsulant film was manufactured.

[0126] In the following Table 1, crosslinking agent compositions used in Examples 1 to 8 and Comparative Example 1 are shown.

[0127] [Table 1]

[0128]

[0129] Experimental example

[0130] A 0.5 mm thick encapsulant film (15 cm x 15 cm) was placed between two release films (thickness: about 100 μm) and laminated and cross-linked in a vacuum laminator at a processing temperature of 150° C. and a processing time of 20 minutes (vacuum 5 minutes / pressure 1 minute / pressure holding 14 minutes).

[0131] (1) Impregnation rate

[0132] Table 2 records the crosslinking agent impregnation completion times measured for Examples 1 to 8 and Comparative Example 1.

[0133] (2) Volume resistance

[0134] The test was conducted at room temperature based on ASTM D257. The prepared sample was placed in a Keithley 8009 resistivity test fixture, a 6517B electrometer / high resistance meter was connected thereto, a voltage of 1000 V was applied, and the volume resistance was measured.

[0135] (3) Vulcanization characteristics

[0136] Based on ASTM D5280, the vulcanization characteristics were measured using a premier MDR from Alpha Technologies. The test was performed at 150°C for 20 minutes, and a torque curve was obtained over time. In this case, the 150°C condition corresponds to the lamination temperature and 20 minutes corresponds to the lamination time. In addition, the difference between the maximum torque (MH) and the minimum torque (ML) applied by the MDR during the corresponding time period was used to compare the vulcanization characteristics of each sample.

[0137] (4) Degree of crosslinking

[0138] Use scissors to cut the cross-linked sheet into 3 x 3 mm 2 Use staples to make 7x 14cm 2The sides and bottom of a 200-mesh wire mesh are sealed. The sheet is injected into the wire mesh, and the weight of the injected sheet is measured. The amount of the sheet is controlled to be 0.49 g to 0.51 g. After the sheet is injected, the top of the wire mesh is sealed with staples, and the total weight of the sample is measured. A solution obtained by dissolving 10 g of butylated hydroxytoluene (BHT) in 1000 g of xylene is poured into a 2L cylindrical reactor, and then three to four samples are injected therein. The reactor is heated, and reflux is terminated 5 hours after the boiling point begins. The sample in the reactor is taken out with a metal drop net and washed with xylene. The sample is dried overnight under vacuum at 100 ° C. The weight of the dried sample is measured, and the degree of crosslinking is calculated. The degree of crosslinking is determined by the average value of three to four samples refluxed in xylene.

[0139] Crosslinking degree (%) = [(sheet weight before reflow) / (sheet weight after reflow)] × 100

[0140] (5) Light transmittance

[0141] The transmittance at 200 nm to 1000 nm was measured using a Shimadzu Uv-3600 spectrophotometer to obtain a transmittance curve, and a value at 280 nm to 380 nm and a value at 380 nm to 1100 nm were determined.

[0142] -Measurement mode: transmittance

[0143] - Wavelength interval: 1nm

[0144] - Measurement rate: Medium

[0145] (6) Measurement of adhesion strength

[0146] 40% of the glass substrate area is covered with an encapsulant film, and the remaining 60% is covered with a polyimide film, and then the fluorine-based solar backsheet is laminated thereon. Lamination is performed at a temperature of 150°C for 20 minutes, so that the encapsulant film is cross-linked and adhered to the glass substrate. A cut is made on the encapsulant film sample with a knife so that the width of the portion to be measured is 1 cm.

[0147] A UTM sample holder and a 1 kN load cell were installed on a tension compression tester (LRX Plus Universal Test Machine, manufactured by LLOYD). Both ends of the encapsulant film were adhered to the glass substrate, and the portion not adhered to the encapsulant film was fixed and pulled at a rate of 60 mm / min to test adhesion.

[0148] [Table 2]

[0149]

[0150] As confirmed in Table 2, if the crosslinking agent composition containing the auxiliary crosslinking compound of Formula 1 in Examples 1 to 8 is used, the impregnation completion time of the crosslinking agent can be shortened compared to Comparative Example 1 using only triallyl isocyanurate as the auxiliary crosslinking agent. In addition, as in Examples 1 to 3, 7 and 8, if a certain amount or more of the auxiliary crosslinking compound of Formula 1 is used together with triallyl isocyanurate as the auxiliary crosslinking agent, the impregnation completion time of the crosslinking agent can be effectively shortened, and a high degree of crosslinking and a high volume resistivity can be achieved.

Claims

1. A crosslinking agent composition for an olefin copolymer, the composition comprising: Cross-linking agent; Silane coupling agents; and The cross-linking aid compound of the following formula 1: [Formula 1] In formula 1, R1 to R4 are each independently an alkyl group of 1 to 20 carbon atoms or an alkenyl group of 2 to 20 carbon atoms, wherein two or more R1 to R4 are each independently an alkenyl group of 2 to 20 carbon atoms.

2. The crosslinking agent composition for olefin copolymers according to claim 1, wherein R1 to R4 are each independently an alkenyl group of 2 to 20 carbon atoms.

3. The crosslinking agent composition for olefin copolymers according to claim 1, wherein R1 to R4 are each independently an alkenyl group of 2 to 8 carbon atoms having a double bond at its terminal.

4. The crosslinking agent composition for olefin copolymers according to claim 1, wherein The auxiliary cross-linking compound of Formula 1 is tetraallyloxysilane. 5 . The cross-linking agent composition for an olefin copolymer according to claim 1 , further comprising a second cross-linking aid compound in addition to the cross-linking aid compound of Formula 1.

6. The crosslinking agent composition for olefin copolymers according to claim 5, wherein The weight ratio of the auxiliary cross-linking compound of Formula 1 to the second auxiliary cross-linking compound is 1:0.2 to 1:9.

0.

7. The cross-linking agent composition for olefin copolymers according to claim 5, wherein The second auxiliary cross-linking compound includes at least one selected from the group consisting of triallyl isocyanurate, triallyl cyanurate, diallyl phthalate, diallyl fumarate, diallyl maleate, ethylene glycol diacrylate, ethylene glycol dimethacrylate, and trimethylolpropane trimethacrylate.

8. The crosslinking agent composition for olefin copolymers according to claim 1, wherein The crosslinking agent is one or more selected from the group consisting of organic peroxides, hydroperoxides and azo compounds.

9. The crosslinking agent composition for olefin copolymers according to claim 1, wherein The crosslinking agent is selected from tert-butyl isopropyl peroxide, di-tert-butyl peroxide, diisopropyl peroxide, 2,5-dimethyl-2,5-di(tert-butyl peroxy)hexane, 2,5-dimethyl-2,5-di(tert-butyl peroxy)-3-hexyne, isopropyl hydroperoxide, diisopropyl hydroperoxide, 2,5-dimethyl-2,5-di(hydroperoxy)hexane, tert-butyl hydroperoxide, bis(3,5,5-trimethylhexanoyl)peroxide, octanoyl peroxide, benzoyl peroxide, o-methylbenzoyl peroxide, 2,0,4-dichlorobenzoyl peroxide, tert-isobutyric acid peroxide, One or more selected from the group consisting of butyl ester, tert-butyl peroxide acetate, 2-ethylhexyl tert-butyl peroxycarbonate (TBEC), tert-butyl peroxide 2-ethylhexanoate, tert-butyl peroxide pivalate, tert-butyl peroxide octanoate, tert-butyl peroxy isopropyl tert-butyl peroxycarbonate, tert-butyl peroxide benzoate, tert-butyl peroxide phthalate, 2,5-dimethyl-2,5-di(benzoylperoxy)hexane, 2,5-dimethyl-2,5-di(benzoylperoxy)-3-hexyne, methyl ethyl ketone peroxide, cyclohexanone peroxide, azobisisobutyronitrile and azobis(2,4-dimethylvaleronitrile).

10. The cross-linking agent composition for olefin copolymers according to claim 1, wherein The silane coupling agent is one or more selected from the group consisting of N-(β-aminoethyl)-γ-aminopropyltrimethoxysilane, N-(β-aminoethyl)-γ-aminopropylmethyldimethoxysilane, γ-aminopropyltriethoxysilane, γ-glycidoxypropyltrimethoxysilane, γ-methacryloxypropyltrimethoxysilane, vinyltrimethoxysilane, vinyltriethoxysilane, 3-methacryloxypropylmethyldimethoxysilane, 3-methacryloxypropylmethyldimethoxysilane, 3-methacryloxypropyltriethoxysilane and p-phenylvinyltrimethoxysilane.

11. An encapsulant composition for an optical device, the composition comprising: Olefin copolymers; and The crosslinking agent composition for olefin copolymers according to claim 1.

12. The encapsulant composition for an optical device according to claim 11, wherein The olefin copolymer is an ethylene / α-olefin copolymer.

13. An encapsulant film for an optical device, comprising a structure derived from an olefin-based copolymer and a compound of the following Formula 1: [Formula 1] In formula 1, R1 to R4 are each independently an alkyl group of 1 to 20 carbon atoms or an alkenyl group of 2 to 20 carbon atoms, wherein two or more R1 to R4 are each independently an alkenyl group of 2 to 20 carbon atoms. 14 . An optoelectronic device comprising an optical device and the encapsulant film for an optical device according to claim 13 .

Citation Information

Patent Citations

  • Manufacturing Method for Gypsum Block Reinforced with Carbon Fiber

    KR1020220085135A

Cited By

  • Insulating material composition, high-voltage cable, preparation method and application

    CN119613848A

  • Insulating material composition, high voltage cable, method of preparation and use

    CN119613848B